Pengaruh Sales Growth, Capital Intensity, Dan Inventory Intensity Terhadap Tax Avoidance - Laela Komalasari; Suharna (GLOBAL SCIENTS PUBLISHER, 2024)
This research aims to analyze the influence of sales growth, capital intensity and inventory intensity on tax avoidance in companies. Tax avoidance is a company's attempt to minimize tax liabilities by exploiting loopholes in tax regulations without breaking the law. Factors such as the influence of sales growth, capital intensity and inventory intensity are thought to have a significant impact on the tax avoidance strategy adopted by the company. The research uses quantitative methods with secondary data obtained from the financial reports of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data analysis technique used is multiple linear regression to test the relationship between the independent variable and the dependent variable. The Sales Growth variable is measured based on the company's revenue growth from year to year, Capital Intensity is measured by comparing fixed assets with total assets, while Inventory Intensity is calculated based on the proportion of inventory to total assets. The research results show that sales growth, capital intensity and inventory intensity simultaneously influence tax avoidance. Partially, sales growth does not show a significant influence on tax avoidance. Capital Intensity was found to have a significant influence, where companies with high capital intensity were more likely to practice tax avoidance. However, Inventory Intensity did not show a significant influence on tax avoidance in this research. Overall, this research provides insight into the factors that influence tax avoidance behavior in companies, as well as practical implications for regulators and company management in understanding the dynamics of tax management.